Research on comprehensive heat transfer performance and structure optimization of swiftlet-type fin of printed circuit heat exchangers - Jinxing Wu; Peng Shao; Jiahui Yi; Shiwu Hou; Tianwei Gu; Dongyang Ding (Annals of Nuclear Energy, 2026)

Achieving fast Zn dynamics in high-mass-loading cathode via 3D-printed hierarchical graphene architectures in zinc-ion batteries - Shixiang Yu; Yongbiao Mu; Huicun Gu; Yonglin Zhang; Shuai Zhao; Haowen Liang; Bowen Hu; Jinxing Sun; Xiaoteng Chen; Lin Zeng; Jiaming Bai; Jinglei Yang (Chemical Engineering Journal, 2025)

A comparison of Chinese soybean collection with European soybean collections on genetic diversity by genome-wide scan - Jiangyuan Xu; Xindong Yao; Yuqing Lu; Rittler Leopold; Yongzhe Gu; Ming Yuan; Yong Zhang; Rujian Sun; Yongguo Xue; Yeli Liu; Dezhi Han; Jinxing Wang; et al. (Genetic Resources and Crop Evolution, 2025)

Phase Segregation-Dictated superior Fe-rich ferrite composite for intensified methane dry reforming with CO2 splitting - Alfred Bekoe Appiagyei; Sasha Yang; Jinxing Gu; Alan Chaffee; Jefferson Zhe Liu; Qinfen Gu; Lian Zhang (Chemical Engineering Journal, 2025)

Investigation of Feeding Effects and Environmental Impact of Fish-Feed Quality: Evidence from Crucian Carp Feeding Experiments - Jiayin Wang; Ran Wu; Jianhua Wang; Jiangtao Guo; Ya Zhang; Nanbing Shi; Jinxing Gu; Yibing Han; Xinyi Guo; Zhe Yu; Guoxi Li; Zhenjiang Yang (Fishes, 2025)
The effects of three types of feed, purchased from online stores and having similar prices, on the growth performance and culture environment of crucian carp (Carassius auratus) were studied in this experiment, which aimed to provide a reference for the evaluation and selection of fish feed. The results showed that feeding different feeds had a significant effect on crucian carp, and that the growth-promoting effect of HD feed (feed produced by Haida Company Limited) was significantly better than that of the other two feeds. For example, the weight gain rate (WGR) of fish in the HD group was 47.1% higher than that in the LD group (p

Facile synthesis of layered spinel ferrite from fly ash waste as a stable and active ketonisation catalyst - Sasha Yang; Jinxing Gu; Binbin Qian; Jim Mensah; Adam F. Lee; Karen Wilson; Barbara Etschmann; Xiya Fang; Jisheng Ma; Qinfen Gu; Lian Zhang (Chemical Engineering Journal, 2024)

Evolution of the Pd0/PdO phase change on Pd-MCM-41 catalyst for efficient production of furfural from the fast pyrolysis of cellulose - Jingwei Wang; Qiaoqiao Zhou; Jinxing Gu; Sasha Yang; Qinfen Gu; Anthony De Girolamo; Lian Zhang (Chemical Engineering Journal, 2024)

Characteristics of conserved microRNAome and their evolutionary adaptation to regulation of immune defense functions in the spleen of silver carp and bighead carp - Yinli Zhao; Jinxing Gu; Ran Wu; Bianzhi Liu; Pengsheng Dong; Guangqing Yu; Daoquan Zhao; Guoxi Li; Zhenjiang Yang (Fish & Shellfish Immunology, 2024)

Cu(II) removal from water by trimercapto-s-triazine trisodium salt modified alkaline lignin - Qiaorui Wang; Fei He; Jinxing Gu; Xuqin Song; Feng Xu (Environmental Science and Pollution Research, 2023)